Bahasa Inggris - Muhammad Ali Najich; Diniy Hidayatur Rahman; Adi Atmoko; Shubby Kaserero; Septinda Rima Dewanti (Pamomong: Journal of Islamic Educational Counseling, 2024)
Social anxiety is common among high school students, impacting their development. This study examines students social anxiety prevalence in Malang, Indonesia. Using a quantitative descriptive survey method, data were collected from 346 students through cluster random sampling. A social anxiety scale based on La Grace's theory was employed to explore in which aspect students social anxiety. The survey revealed that beliefs in negative assessments (37%) were the highest, followed by social avoidance of new situations (36%) and general social avoidance (27%). Overall, social anxiety in this group is moderate. This study discuss that embedding Islamic and cultural values to address student’s social anxiety may provide effective support for Guidance and Counseling services. Future research should investigate specific values for interventions and consider longitudinal studies to understand their long-term effects.